Weightlifting: Program design - Stone, M. H.; Pierce, K. C.; Sands, W. A.; Stone, M. E. (Strength and Conditioning Journal, 2006)
This is the second part of a 2-part discussion (the first,"Weightlifting:A Brief Overview," appeared 28(1):50-66, 2006) on weightlifting and will describe the best methods of designing a weightlifting program.